Depriving the Deprived: A Narrative Review of Brain Drain of Health Professionals from Low- and Middle-Income (LMICs) to High Income Countries through an Equity Lens - Jahun, Ibrahim; Udod, Sonia; Roskoshnyi, Illia; Yakubu, Aminu; Sanusi, Muhammad; Aliyu, Gambo (British Journal of Healthcare and Medical Research, 2026)
With an estimated population of 7.8 billion, health professionals (HPs) are grossly inadequate globally and far below the WHO’s benchmark of one physician, four nurses per 1000 population. Despite hosting 11% of the world’s population and 24% of the global burden of diseases, Sub-Saharan Africa (SSA) has the most significant health professional HPs shortages. The prolonged haemorrhage of HPs from SSA and other low and middle-income countries (LMICs) to Organization for Economic Co-operation and Development (OECD) member states continues to complicate health equity in LMICs. This has raised concerns about social justice and breach of ethics. A narrative review approach was used to appraise the brain drain situation in Egypt, Nigeria, and South Africa, countries most affected by the phenomenon. The review showed that between 2016 and 2019, Egypt lost over 10,000 physicians. Nigeria also experienced a significant brain drain, with over 16,000 doctors and 75,000 nurses emigrating in the past five years (2020 – 2025). South Africa faced a physician density drop from 0.8 to 0.31 per 1,000 people in a year. A global shared responsibility is required to mitigate the worsening brain-drain of physicians and nurses from African LMICs to High Income Countries such as the OECD. Collaborative framework between OECD member states and LMICs that allows for a fairer and mutually beneficial HPs emigration regime is proposed in this review. A role for the World Health Organization, and other international public health institutions, is further suggested to propose and promote sustainable innovative strategies to ensure justice, fairness, and equity in reversing the exodus of HPs from LMICs. Although strengthening health systems in African countries is vital, sustainable progress depends highly on collaborative partnerships with OECD countries to co-invest in expanding capacity building, educational infrastructure, and the adoption of technology-enabled learning in the LMICs.